Hybrid Cryptography for Random-key Generation based on ECC Algorithm - P. Gayathri; Syed Umar; G. Sridevi; N. Bashwanth; Royyuru Srikanth (International Journal of Electrical and Computer Engineering (IJECE), 2017)
As more increase in usage of communications and developing them more user friendly. While developing those communications, we need to take care of security and safety of user’s data. Many researchers have developed many complex algorithms to maintain security in user’s application. Among those one of the best algorithms are cryptography based, in which user will be safe side mostly from the attackers.  We already had some AES algorithm which uses very complex cryptographic algorithm to increase the performance and more usage of lookup tables. So the cache timing attackers will correlates the details to encrypt the data under known key with the unknown key. So, for this we provide an improvised solution. This paper deals with an extension of public-key encryption and decryption support including a private key. The private key is generated with the combination of AES and ECC. In general AES, key length is 128 bits with 10 times of iterations. But with this, users won’t get efficient security for their operations, so to increase the security level we are implementing 196-bit based encryption with 12 times round-key generation iterations. By this enhancement, we can assure to users to high level security and can keep users data in confidential way.